2019
DOI: 10.3390/min9070436
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Sources of Minerals and Their Impact on the Hydrocarbon Reservoir Quality of the PaleogeneLulehe Formation in the Eboliang Area, Northern Qaidam Basin, China

Abstract: The Lulehe sandstone in the Eboliang area is a major target for hydrocarbon exploration in the northern Qaidam Basin. Based on an integrated analysis including thin section analysis, scanning electron microscopy, X-ray diffraction, cathodoluminescence investigation, backscattered electron images, carbon and oxygen stable isotope analysis and fluid inclusion analysis, the diagenetic processes mainly include compaction, cementation by carbonate and quartz, formation of authigenic clay minerals (i.e., chlorite, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Where expulsion of petroleum is not retarded by low rock permeability, high pore pressure does not develop, organic porosity compacts and kerogen shrinks, and hence the source rock thins, causing fracturing (Brown, 2000). Maturation of kerogen and decarboxylation of organic matter may release CO 2 (Chen B. et al, 2019).…”
Section: Shales/mudstones/claystonesmentioning
confidence: 99%
“…Where expulsion of petroleum is not retarded by low rock permeability, high pore pressure does not develop, organic porosity compacts and kerogen shrinks, and hence the source rock thins, causing fracturing (Brown, 2000). Maturation of kerogen and decarboxylation of organic matter may release CO 2 (Chen B. et al, 2019).…”
Section: Shales/mudstones/claystonesmentioning
confidence: 99%
“…The evidence was the high calcium level recorded for 7 days of immersion for HApS2 in SBF relative to that of HApS1. The high pH value of 12.6 after dissolution suggested that calcium mineral was in association with carbonate [32]. The solution reached a supersaturation and interacted with phosphate in solution to form amorphous calcium phosphate (ACP) [14].…”
Section: -mentioning
confidence: 99%
“…The Paleocene turbidite sandstones of the Central North Sea contain about half of the total recoverable oil reserves within the region (2.99 billion barrels), with estimated reserves of approximately 6.01 billion barrels (Brennand et al, 2009). Therefore, quantitative evaluation of the sandstones reservoir quality is crucial for understanding of reserve estimations and development of continued hydrocarbon production strategies (Chen et al, 2019;Marchand et al, 2015;Morad et al, 2010). Reservoir quality is strongly influenced by depositional parameters (e.g., primary sediment composition, grain size, sorting, and clay content, which constitute depositional facies) (Bell et al, 2018;Marchand et al, 2015;Porten et al, 2016;Stammer, 2014) and diagenetic alterations (Morad et al, 2010;Oluwadebi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%